Landscape effects on gene flow of the Brown bear (Ursus arctos) on the Cantabrian Mountains - Barbosa, Ana Rute Silva (2022)
As one of the smallest populations in Europe, the Cantabrian brown bear population is threatened, isolated and fragmented in two subpopulations. Despite the low connectivity between both subpopulations, the Cantabrian brown bear population has been recovering over the years and is the only one in Europe that has not been subject to populations reinforcements. However, a difference in the recovery rates has characterizes these two subpopulations (Western and Eastern) over the years. Understanding the environmental features that may be shaping the ecological characteristics of the subpopulations in the Cantabrian range, such as patterns of gene flow along their distribution, are of extreme importance for their conservation and recovery. In this study, microsatellites (nuclear autosomal markers and sex markers) were used to investigate the genetic structure of subpopulations. This analysis was carried out by assessing the correlation between genetic differences and landscape resistance models. Several functional relationships between genetic distances, land cover, temperature, elevation and human disturbance were also analyzed, thus testing for isolation by resistance (IBR) within each subpopulation. Additionally, isolation by distance (IBD) within each population was tested. All hypotheses were tested according to the reciprocal causal modelling method. Results show that agriculture/pastures (hyp2), agriculture/pastures + open areas (hyp13) and forest + agriculture/pastures (hyp9) were the supported landscape resistance models by reciprocal causal modelling, applied in each subpopulation. In the Western subpopulation hyp13 demonstrate the highest relative support (0.040441), and the model contained in this hypothesis was considered as the best. Gene flow in Western subpopulation is maximum in agriculture/pastures + open areas (Agr+Open) whereas in Eastern subpopulation is maximum in forest + agriculture/pastures (Forest+Agr). Western brown bears are dependent of ecosystems where agricultural, pasture and open areas covers are predominant. Eastern brown bears are dependent of ecosystems where forested, agricultural and pasture covers are most prominent. This study reveals a difference between the features that are drivers to gene flow in both subpopulation and provides new insights on the patterns of gene flow in the Cantabrian brown bear subpopulation. Conservation strategies are important to ensure the subpopulations viability and results obtained here will assist in the definition of new measures, thus promoting a more effective recovery of the threatened Cantabrian Mountain population.